Establishment of Brachiaria brizantha cv. Marandu, under levels of soil water availability in stages of growth of the plants - Leandro Coelho de Araujo; Patrícia Menezes Santos; Fernando Campos Mendonça; Gerson Barreto Mourão (Revista Brasileira de Zootecnia, 2011)
The objective of this work was to evaluate yield traits and development of palisadegrass under the influence of water deficit during the establishment period. The experiment was carried out in a greenhouse, in a completely random block statistical design in a factorial arrangement and additional treatment (3 × 3 + 1). The treatments referred to the suppression of irrigation at different phases of the establishment (sowing, germination and initial tillerring) until the soil presented water content of 75%, 50%, and 25% of the moisture related to field capacity (qFC), besides control treatment with no water restriction. Evaluations of number of grown tillers per vase, green leaves per tiller and plant height were carried out weekly, for five weeks after the first tillers appeared. Biomass sampling was carried out approximately 30 days after the end of the last applied treatment, when the soil was kept close to 100% of field capacity relative moisture. Tillering and biomass yield of palisadegrass during establishment phase are reduced when water deficit is sufficient to make soil content water reach 25% of relative moisture field capacity, regardless to the season when water shortage takes place.